The Concept of Ideal Islamic Boarding School Leadership Perspective KH Abdullah Syukri Zarkasyi (1985-2020) - Awaluddin Faj; Hendri Tanjung; Budi Handrianto (Universitas Ibn Khaldun Bogor, 2022)
This study aims to determine the Concept of Ideal Islamic Boarding School Leadership today from the point of view of KH Abdullah Syukri Zarkasyi who has experience in developing the Darussalam Gontor Modern Islamic Boarding School from 1985-2020. This Research used a qualitative methodology with a phenomenological approach, with a field of exploration and a theoretical orientation or theoretical perspective, namely the researcher understood, described and analyzed the Concept of Ideal Islamic Boarding School Leadership. The results showed that the idea of Islamic boarding school leadership from the perspective of KH Abdullah Syukri Zarkasyi was considered the most appropriate and ideal to be developed in organizational culture and modern Islamic boarding schools, because the ideal type of Islamic boarding school leadership must be based on the principles of leadership values that must be owned by a leader, including: 1). The values of sincerity, 2). Honesty, 3). Sacrifice, 4). Moslem brotherhood, 5). Exemplary values, 6) Optimism